Blockchain technology applications in businesses and organizations - Giovanni, Pietro De (IGI Global, 2022)
"This book investigates the true advantages that blockchain entails for firms by creating transparent and digital transactions, resolving conflicts and exceptions, and providing incentive-based mechanisms and smart contracts.